Anura of Jebel Al Dayer Biosphere Reserve, Sudan - Rahman , Mohmed A. Abd El; Mahmoud , Zuheir N.; Salih, Mohamed A. (Innovations in Biological Science Vol. 5, 2024)
5,423 anuran specimens falling into nine species, seven genera and six families were collected from Jebel Al Dayer Biosphere Reserve. Sclerophrys pentoni, Sclerophrys xeros, Hemisus marmoratus, Tomopterna milletihorsini, Hildebrantia ornata and Kassina senegalensis were found throughout autumn. Higher numbers were recorded by S. pentoni during autumn, for T. milletihorsini during early winter. Juveniles outnumbered adults during early winter. Sclerophrys pentoni and S. xeros were observed in all habitats. Leptopelis bocagii was found only in the mountain-forest/slope and from 5 to 1200m; Hildebrantia ornata was found in residential areas; Ptycadena schillukorum and Hemisus marmoratus were found in swampy habitats. Sclerophrys xeros was found from 0-500m elevation, and Ptychadena schillukorum, T. milletihorsini, S. regularis and H. ornata from 0-5 m. The Least Significant Differences test showed significant (p>0.05) to insignificant (p<0.05) differences in the number of anurans between seasons, habitats and elevations. Tomopterna milletihorsini from Jebel Al Dayer Biosphere Reserve is a new record for Sudan.